Coral content, radiocarbon dating, geochemistry, benthic foraminifera and grain size distribution in sediment cores CE18011_VC1 and RH17002_VC7 - Luke O extquotesingleReilly (PANGAEA, 2022)
A remotely operated vehicle mounted (ROV) vibrocorer rig acquired the two cores from the Porcupine Bank Canyon (NE Atlantic) and western Porcupine Bank (NE Atlantic) during the RH17002 and CE18011 research cruises. RH17002_VC7 is a 0.81 m ROV-vibrocore and was acquired from a cold-water coral mound summit on lip of the Porcupine Bank Canyon. CE18011_VC1 is a 1.30 m ROV-vibrocore and was acquired from cold-water coral mound summit on the western Porcupine Bank. Coral content and coral clast size were determined using three-dimensional computed tomography. To construct a geochronological framework, mixed benthic foraminifera (Cibicides lobatulus, Cibicides refulgens and Discanomalina coronata), monospecific planktic foraminifera (Globigerina bulloides) and cold-water coral pieces (Madrepora oculata) were subjected to radiometric analysis. Results were standardized using PaleoDataView (Langner and Mulitza, 2019) to allow applicability and consistency across synthesis. Benthic foraminifera assemblages were analysed from both cores. Their abundances were used to infer paleoenvironmental signals between 9.1 to 5.6 ka BP, and used concurrently with coral content percentages derived from computer tomography. The data was collected by identifying and counting benthic foraminifera from the >125 μm fraction of sediment from the cores. Grain size analysis of the siliclastic fraction of the sediment were used to infer changes in hydrodynamic regime (i.e. mean grain size and mean sortable silt size). δ13C and δ18O were determined from planktic foraminifera (Globigerina bulloides) and benthic foraminifera (Cibicidoides pachyderma) to infer watermass variation.